Geographies of capital punishment: New directions and interventions. Issue 12 (1st October 2020) - Colucci, Alex R.
Abstract: A thorough analysis of capital punishment from a political–geographical perspective is lacking in the discipline of geography. This is despite the fact that capital punishment overlaps with numerous geographic approaches, concepts, and areas of study. This study serves as a call to geographers to begin considering capital punishment's wide interaction and interrelation with developed areas of knowledge in the discipline. Specifically, political geographers stand to contribute in novel ways to wider discussions about capital punishment by analyzing executions relative to contemporary work in geography on violent, legal, and carceral spaces. I first introduce the need for geography's engagement with this pressing issue. Then, I clarify several terms needed to understand this violent practice. A third section highlights several pathways of development in the critical geographies of capital punishment. It is organized around four broad themes—critically mapping capital punishment, bodies in motion, politics of access, and executing the "other"—connecting capital punishment to developing concepts, literatures, and subdisciplines in geography. The final two sections outline an epistemological approach to the geographies of capital punishment and how legal and carceral geographies might contribute.